Epidemiology of Campus Football Injuries in Ningxia, China: Occurrence, Causes, and Management - Liu, Hengyuan; Huang, Sen; Bu, Te; Jiang, Wei; Fu, Tao; Zhao, Liliang (Frontiers in Public Health, 2022)
Objective: By 2022, the Chinese government intends to have more than 30 million primary-, middle- and high-school children and adolescents regularly participate in campus football. In contrast, epidemiology of campus football injuries is completely missing. The goal of this descriptive epidemiological study was to determine the current state of campus football injuries and then to recommend appropriate prevention and management strategies. Methods: This retrospective epidemiological study conducted a survey of students, physical education and football teachers in primary, middle and high schools in the Ningxia Autonomous Region to determine the campus football injuries that occurred throughout the preceding 12-month period. The survey comprised questions on demographic characteristics, the occurrence, causes, and management of campus football injuries. Results: A total of 1285 students and 200 teachers returned eligible surveys. 25.7% of students had encountered injury accidents while participating in campus football activities. 31.3% of high school students, 23.8% of middle school students, and 19.2% of primary school students have sustained injuries. Football competition, accounting for 45.4% of all injuries, is the leading cause of injury. Football class teaching, which accounted for 3.0% of all injuries, had the lowest injury rate of any campus football activity. Students and teachers reported that a lack of safety awareness and injury prevention education were the primary causes of injuries. Only 18.7% and 11.4% of students are familiar with first aid basics and cardiopulmonary resuscitation, respectively. 10.6% and 7.5% of students lack any first aid basics and skills, respectively. 43.9% of students lack insurance coverage for athletic injuries. 62.5% and 38.5% of teachers reported that schools lack first aid training and an emergency plan for injuries, respectively. Conclusion: Students in Ningxia’s campus football programs have a high injury risk. Injury prevention and management strategies lag significantly behind the mainstream nationwide promotion of campus football in China.